2021
DOI: 10.1002/jctb.6655
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of recoverable magnetic composite material based on graphene oxide for fast removal of lead and cadmium ions from aqueous solution

Abstract: BACKGROUND In this study, a novel magnetic material was applied as an adsorbent for simultaneous removal of Pb(II) and Cd(II) ions from aqueous solutions. The adsorbent was synthesized using functionalized MnFe2O4 magnetic nanoparticles grafted to lamellar graphene oxide surface (MnFe2O4@SiO2‐NH2@GO) and characterized using X‐ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, thermogravimetric analysis and magnetic measurements. RESULTS The adsorbent exhibited superior adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…After adsorption of Pb (II), the binding energy of -NH 2 and -NH 3 + are remarkably shifted to 400.1 eV and 402.2 eV, respectively (Fig. 11f), which is due to the lone pairs of N coordinate with Pb (II) ions lead to the surrounding electron cloud density decreased and the binding energy increased [74].…”
Section: Adsorption Mechanismmentioning
confidence: 97%
“…After adsorption of Pb (II), the binding energy of -NH 2 and -NH 3 + are remarkably shifted to 400.1 eV and 402.2 eV, respectively (Fig. 11f), which is due to the lone pairs of N coordinate with Pb (II) ions lead to the surrounding electron cloud density decreased and the binding energy increased [74].…”
Section: Adsorption Mechanismmentioning
confidence: 97%
“…However, these prepared nanocomposites possess a higher removal efficiency at a shorter contact time than those of other nanocomposites reported in the literature, where graphene-structure materials in combination with magnetic ferrites (such as GO/Fe 3 O 4 , MnFe 2 O 4 @SiO 2 -NH 2 @GO) were used as adsorbents. 7,44 This indicated that C GO /MCF nanocomposites could serve as valuable adsorbents for Cd 2+ removal in a short contact time. Therefore, the contact time of 20 min was chosen for the subsequent experimentations.…”
Section: Resultsmentioning
confidence: 93%
“…Yet, a higher Cd 2+ adsorption capacity was estimated for the studied nanocomposites than grapheneferrite composite materials reported in the literature. 44,46 Adsorption kinetic and isotherm studies…”
Section: Adsorption Propertiesmentioning
confidence: 99%
“…The Langmuir model fits better the experimental data, in comparison to the Temkin and Freundlich isotherm models, because of the higher correlation coefficients, suggesting a monolayer adsorption. This indicates that the surfaces are homogeneous and all adsorption sites are equivalent 14,61 . In order to evaluate how suitable the adsorbent is towards the adsorbate investigated, a separation factor constant ( R L ) (Eqn (15)) was applied.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the surfaces are homogeneous and all adsorption sites are equivalent. 14,61 In order to evaluate how suitable the adsorbent is towards the adsorbate investigated, a separation factor constant (R L ) (Eqn ( 15)) was applied. The constant R L (which is dimensionless) enables us to infer if the process of adsorption is favorable or not.…”
Section: Intraparticle Diffusion Model or Weber-morris Kinetic Modelmentioning
confidence: 99%